DIVERSITAS, KARAKTERISTIK HABITAT ROOSTING, DAN ANALISIS MANGSA ALAMI KELELAWAR SUBORDO MICROCHIROPTERA PENGHUNI GUA DI KAWASAN KARST TUBAN DAN KARST MENOREH - , Tatag Bagus Putra Prakarsa ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Indonesia called as Megabiodiversity Countries. Variation of landscape, altitude and latitude, and the archipelago form supported the large biodiversity of Indonesia. One of landscape variation is karstic area, including Tuban and Menoreh karstic area. Karstic area has biodiversity uniqueness in endokast and exokarst. Microchiropteran bat is a part of biodiversity in endokarst. This research were aimed to determine difference level of bats-cave diversity in Tuban and Menoreh karstic area, determine roosting habitat caracteristic of bats-cave in Tuban and Menoreh karstic area, and determine prey biomass of bats-cave in Tuban and Menoreh karstic area in one night. The research began in July until October 2012 in 12 cave of Tuban and Menoreh karstic area. The selection of caves by physical and geomorphological condition, that representative all of caves at each karstic area. The diversity is measured by Shimpsonâs diversity index, roosting habitat caracteristic based on cave microclimatic, chamber depth from entrance, high of roosting site, wide of roosting site, texture of roosting site, and pre biomass of bats-cave were measured by the ratio of body weight before and after hunting prey. Generally, microchiropteran bats-cave diversity in Menoreh is higher than Tuban karstic area. But, taksic diversity in Tuban higher than Menoreh karstic area. There are two groups microchiropteran bats-cave in Tuban and Menoreh karstic area based on roosting habitat caracteristic, namely cosmopolite roosting site and specific roosting site. Roosting of bats-cave was influenced by many factors, they are damage of cave ecosystem and the environment around the cave, intensity of human disturbance to the cave, near the source of prey, roosting site competition, and there is a water source or close to water sources. The average Microchiropteran bats in Tuban and Menoreh karstic area able to prey 29.15% of their body weight. Some species are able to prey up to 2.5 from the body weight. All population of bats-cave in Tuban and Menoreh karstic area able to prey 263,201,290 individual of insects in one night.